INDOBARCA IDENTITY CONSTRUCTION (INDOBARCA CHAPTER JAKARTA, BANDUNG AND JOGJA) ON INSTAGRAM - Pratomo, Muhammad Nazrie (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
This research discusses identity construction by the Jakarta, Bandung, and Jogja chapters of IndoBarca on their Instagram accounts. Football is a sport that is popular with people all over the world. FC Barcelona is a football club from Catalonia, Spain, with many followers from various parts of the world. FC Barcelona has an official community from multiple countries, including Indonesia, namely IndoBarca. IndoBarca holds the Penya title, which was given directly by FC Barcelona as an official community and, to this day, a chapter (representative, section) in almost all of Indonesia. This research aims to discover how para chapter from the IndoBarca community build their identity on Instagram. This research uses observations on each of the three Instagram accounts IndoBarca and data collection techniques through documentation and observation. The research results show that each chapter of IndoBarca is trying to construct its identity differently from chapter other. To show every chapter using regional icons in the middle of the IndoBarca logo, using specific colors for content uploaded on Instagram, differentiating content from attributes membership, and carrying out activities (events) for members. Keywords: Identity Construction, Social Media, Community.